Enhancing protein production and growth in chinese hamster ovary cells through miR-107 overexpression - Maryam Jari; Shahriyar Abdoli; Zahra Bazi; Fatemeh Tash Shamsabadi; Farnaz Roshanmehr; Majid Shahbazi (AMB Express, 2024)
Abstract Chinese Hamster Ovary (CHO) cells are widely employed as host cells for biopharmaceutical production. The manufacturing of biopharmaceuticals poses several challenges, including restricted growth potential and inadequate productivity of the host cells. MicroRNAs play a crucial role in regulating gene expression and are considered highly promising tools for cell engineering to enhance protein production. Our study aimed to evaluate the effects of miR-107, which is recognized as an onco-miR, on erythropoietin-producing CHO cells (CHO-hEPO). To assess the impact of miR-107 on CHO cells, a DNA plasmid containing miR-107 was introduced to CHO-hEPO cells through transfection. Cell proliferation and viability were assessed using the trypan blue dye exclusion method. Cell cycle analysis was conducted by utilizing propidium iodide (PI) staining. The quantification of EPO was determined using an immunoassay test. Moreover, the impact of miR-107 on the expression of downstream target genes was evaluated using qRT-PCR. Our findings highlight and underscore the substantial impact of transient miR-107 overexpression, which led to a remarkable 2.7-fold increase in EPO titers and a significant 1.6-fold increase in the specific productivity of CHO cells (p < 0.01). Furthermore, this intervention resulted in significant enhancements in cell viability and growth rate (p < 0.05). Intriguingly, the overexpression of miR‑107 was linked to the downregulation of LATS2, PTEN, and TSC1 genes while concurrently driving upregulation in transcript levels of MYC, YAP, mTOR, and S6K genes within transgenic CHO cells. In conclusion, this study collectively underscores the feasibility of utilizing cancer-associated miRNAs as a powerful tool for CHO cell engineering. However, more in-depth exploration is warranted to unravel the precise molecular intricacies of miR-107's effects in the context of CHO cells.